Avatars in Edinburgh: The Private Memoirs and Confessions of a Justified Sinner and the Second Life of Hogg’s Ettrick Shepherd - George, Jacqueline (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2012)
In this essay, I deploy the contemporary technical term avatar to interpret the functions of “the Ettrick Shepherd,” a character associated with James Hogg that originated in Blackwood’s Edinburgh Magazine and appears subsequently in Hogg’s novel The Private Memoirs and Confessions of a Justified Sinner (1824). The notorious difficulty of Sinner, I argue, is due in part to the movement of the Shepherd, as an avatar, from one textual realm to another in a way that reveals the limits of meaning making in synthetic landscapes. I show how reading the Shepherd as an avatar furthers our understanding of the novel’s engagement with Blackwood’s, as well as the experience of readers in Romantic-era Edinburgh, whose literary culture thrived on dynamic representations of and relationships between people in print.